PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ANIMASI POWTOON TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS III SDN GUDANG TIGARAKSA - Indah Yuliarti Sari; Alberth Supriyanto Manurung (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the creative thinking ability of students using media powtoon. This type of research uses a method quasi experimental with a design nonequivalent control group in using two classes of samples. This research is a quantitative by giving treatment to a class that will be compared with the control class. The instrument in this study used a test and observation sheets. The data analysis technique of students creative thinking results was using t-test statistical analysis and the use of media powtoon with percentage analysis. The results of this study indicate that the average value of pretest the experimental class is 47.50 and the control class is 47.50 while the average of posttest the experimental class is 82.50 and the control class is 73.06 and based on the measurement of the Independent Sample T-Test obtained Sig value 0.000 < 0.5 which means there is a significant difference, it can be concluded that the hypothesis is accepted, which means that there are differences in the results of posttest the experimental and control classes. Based on these results, it can be concluded that there is a significant effect of using media powtoon of students creative thinking skills.